Experimental aspects of biomass fuels in a bubbling fluidized bed combustor - dos Santos, Francisco Jose [UNESP]; Goldstein, Leonardo (Elsevier B.V. Sa, 2008)
This work presents experimental information relevant to the combustion of biomass in a bubbling fluidized bed. The biomass distribution in a fluidized bed was studied through tests performed in a cold bed, while the volatiles released in the biomass pyrolysis, the burning rate of the resulting charcoal, and the combustion control regime, were studied through tests performed in a high temperature bed.Visual examination of photographs taken from a transparent walls bed, with a rectangular cross-section, showed that the large fuel particles, typical of biomass processing, were distributed in the bubbles, in the splash zone, and in the emulsion phase. The occurrence of biomass in the emulsion phase was favored by burning biomass particles of greater density and smaller size-expetimentally determined in each case. Decreasing the fuel particle size improved the biomass distribution inside the bed. The same was accomplished by increasing the superficial gas velocity as high as possible, compatibly with the acceptable elutriation.Burning tests showed that the biomass fuels have the advantage of reaching the diffusional regime at temperatures that can be lower than 1000 K, which ensures that the biomass fuels burn in a stable regime. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: biomass; combustion characteristics; bubbling fluidized beds; volatiles release; burning rate